2019
DOI: 10.1186/s13046-019-1096-0
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of tumor suppressor long noncoding RNAs in breast cancer

Abstract: Background The landscape and biological functions of tumor suppressor long noncoding RNAs in breast cancer are still unknown. Methods Data from whole transcriptome sequencing of 33 breast specimens in the Harbin Medical University Cancer Center cohort and The Cancer Genome Atlas was applied to identify and validate the landscape of tumor suppressor long noncoding RNAs, which was further validated by The Cancer Genome Atlas pancancer data including 33 cancer types and 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 59 publications
1
37
0
1
Order By: Relevance
“…A combined lncRNA-focus expression signature (LFES) that included 10 additional lncRNAs functioned as a superior unfavorable prognostic factor (AUC = 0.887) [19]. The other study, however, identified ACVR2B-AS1 as an independent favorable prognostic factor in breast cancer [20]. Our study revealed that ACVR2B-AS1 is an adverse factor in liver cancer.…”
Section: Discussionmentioning
confidence: 82%
“…A combined lncRNA-focus expression signature (LFES) that included 10 additional lncRNAs functioned as a superior unfavorable prognostic factor (AUC = 0.887) [19]. The other study, however, identified ACVR2B-AS1 as an independent favorable prognostic factor in breast cancer [20]. Our study revealed that ACVR2B-AS1 is an adverse factor in liver cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Pang et al identified the landscape of tumor suppressor lncRNAs in 33 breast cancer specimens using whole transcriptome sequencing, and they validated the results with a TCGA dataset [23]. These authors identified multiple lncRNAs that were negatively regulated at the transcriptional level by epigenetic modifications such as DNA methylation and histone modification [23]. He et al found that lncRNA AFAP1-AS1 expression correlated negatively with the promoter CpG methylation status in both lung cancer cells and patient tissues, and the DNA methyltransferase inhibitor decitabine significantly increased AFAP1-AS1 expression [24].…”
Section: Discussionmentioning
confidence: 96%
“…Yang et al showed that lncRNA GAS5 expression was decreased in parallel with increased GAS5 methylation in cervical cancer cells, and forced overexpression of GAS5 inhibited the growth and metastatic behavior of the cells [22]. Pang et al identified the landscape of tumor suppressor lncRNAs in 33 breast cancer specimens using whole transcriptome sequencing, and they validated the results with a TCGA dataset [23]. These authors identified multiple lncRNAs that were negatively regulated at the transcriptional level by epigenetic modifications such as DNA methylation and histone modification [23].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, increasing evidence have shown that cellular events, including differentiation, proliferation, invasion, apoptosis, and migration, have all been associated with lncRNAs (Guttman et al, 2011). Additionally, there has been new evidence suggesting that lncRNAs may regulate a variety of biological and disease processes, from gene transcription and translation to post-translational modifications (Davalos and Esteller, 2019;Pang et al, 2019). More importantly, lncRNAs have been reported to be used as tumor suppressor genes or oncogenes, thus affecting the proliferation and metastasis of various types of tumors during tumorigenesis (Chen Q. N. et al, 2017;Lu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%